Optimisation of extrusion conditions for production of antioxidant-rich extruded breakfast cereals from purple sweet potato (Ipomoea batatas l.) and red rice using response surface methodology - Senevirathna, Sri Sampath Janaka; Ramli, Nurul Shazini; Azman, Ezzat Mohamad; Juhari, Nurul Hanisah; Karim, Roselina (Universiti Putra Malaysia, 2023)
Purple sweet potato powder (PSPP) is rich in anthocyanins and other polyphenols that provide excellent antioxidant and other biological activities with potential health benefits. In the present work, the response surface methodology (RSM) was used to optimise the extrusion processing conditions to develop healthy breakfast cereals. The independent variables studied included barrel temperature, screw speed, and feed moisture. The linear terms of barrel temperature and feed moisture content were found to be the significant (p < 0.05) factors affecting the product's functional and physicochemical properties. The expansion property of extrudate significantly (p < 0.001) increased at low temperature, high screw speed, and low feed moisture. The recommended optimum extrusion conditions of barrel temperature, screw speed, and feed moisture content were at 157.0°C, 126.0 rpm, and 13.0%, respectively; and under these optimum conditions, significantly high retention (75.0%) of anthocyanin content was detected. Furthermore, scanning electron micrographs depicted that the optimised breakfast cereals had a better cell structure with smoother and thinner cell walls than the non-optimised samples.